1998
DOI: 10.1016/s1074-7613(00)80535-x
|View full text |Cite
|
Sign up to set email alerts
|

The Death Domain Kinase RIP Mediates the TNF-Induced NF-κB Signal

Abstract: The death domain serine/threonine kinase RIP interacts with the death receptors Fas and tumor necrosis receptor 1 (TNFR1). In vitro, RIP stimulates apoptosis, SAPK/JNK, and NF-kappaB activation. To define the physiologic role(s) that RIP plays in regulating apoptosis in vivo, we introduced a rip null mutation in mice through homologous recombination. RIP-deficient mice appear normal at birth but fail to thrive, displaying extensive apoptosis in both the lymphoid and adipose tissue and dying at 1-3 days of age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
876
11
4

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,031 publications
(957 citation statements)
references
References 43 publications
41
876
11
4
Order By: Relevance
“…Upon binding to its surface receptors TNFRI or TNFRII, TNFa induces receptor trimerization and recruitment of death domain-containing adaptor protein TRADD to the receptor's cytoplasmic death domains. The subsequent recruitment of RIP and TRAF2 leads to activation of downstream kinases and signaling through the IKK/NF-kB and JNK/AP-1 pathways (Yeh et al, 1997;Kelliher et al, 1998;Lin et al, 2000). We found that the upregulation of TMS1 by TNFa was dependent upon the activities of both the NF-kB and JNK signaling pathways, and in particular required the p65/RelA subunit of NF-kB.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Upon binding to its surface receptors TNFRI or TNFRII, TNFa induces receptor trimerization and recruitment of death domain-containing adaptor protein TRADD to the receptor's cytoplasmic death domains. The subsequent recruitment of RIP and TRAF2 leads to activation of downstream kinases and signaling through the IKK/NF-kB and JNK/AP-1 pathways (Yeh et al, 1997;Kelliher et al, 1998;Lin et al, 2000). We found that the upregulation of TMS1 by TNFa was dependent upon the activities of both the NF-kB and JNK signaling pathways, and in particular required the p65/RelA subunit of NF-kB.…”
Section: Discussionmentioning
confidence: 78%
“…This is achieved through binding of TNFa to the TNFa receptor (TNFR), which in turn recruits TRADD and RIP or TRAF2 to induce activation of the IKK complex (Natoli et al, 1997;Kelliher et al, 1998) and JNK (Yeh et al, 1997) respectively. Previous reports have suggested that TMS1 can either promote or inhibit NF-kB signaling depending on cell type, the coexpression of specific adaptor proteins and/or TMS1 expression levels Manji et al, 2002;Stehlik et al, 2002;Wang et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…TRAFs may either recruit the IKK complex directly (Devin et al, 2001) or indirectly through the serine/threonine kinase, RIP1. RIP1 can also interact independently with TRADD and is an essential adapter for TNF-induced NF-kB activation and protection from apoptosis (Hsu et al, 1996;Ting et al, 1996;Kelliher et al, 1998;Devin et al, 2000). Upon ubiquitination, RIP1 can bind directly to NEMO and recruit IKK independent of TRAF2 (Zhang et al, 2000).…”
Section: Tnf-r Superfamily Signalingmentioning
confidence: 99%
“…RIP has never been shown to co-immunoprecipitate with TNF-R1 whereas it does with LMPI. RIP is required for TNF-R1-mediated activation of NF-kB, but it is not required for LMP1-mediated activation of NF-kB (Kelliher et al, 1998;Ting et al, 1996). LMP1-mediated activation of NF-kB is identical in both RIP-expressing and RIPde®cient Jurkat cell lines (Izumi et al, 1999).…”
Section: Lmp1 Activates Rel/nf-kb Through Tnf-r Associated Signaling mentioning
confidence: 99%